Design And Building Of The Utility Performance Monitoring System At PT. XYZ With Brainstorming Method - Kadek Suarjuna Batubulan; Mungki Astiningrum; Dika Rizky Yunianto (International Journal of Health Engineering and Technology, 2024)
In general, utilities in engineering are devices or systems designed to provide basic needs or to help complete certain jobs or processes. In engineering, utilities generally refer to systems or devices designed to provide basic needs such as electricity, water, gas, or telecommunications. At PT. The brainstorming method is used to produce creative ideas that can be applied in developing utility monitoring systems. Various ideas are generated through discussion and debate between brainstorming participants. Then, these ideas are analyzed and selected to select those that best suit PT XYZ's needs. Therefore, the author created a utility performance monitoring system to make it easier for the engineering department to carry out work activities. This utility performance monitoring system was created using a JavaScript framework, namely AngularJS for the frontend and ExpressJS for the backend. Apart from that, the author also tested PT XYZ employees so that the system runs according to needs. Of the 10 respondents, more than 50% of the accumulated respondents stated that the utility performance monitoring system application was running satisfactorily and very satisfactorily, there were 10% to 30% of respondents who stated that it was running well and 10% of respondents said it was not working well. Based on the test results above, it was found that the utility monitoring system at PT XYZ could be categorized as a fairly informative information system for the engineering department.